2021
DOI: 10.1101/2021.04.16.440223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post mortem mapping of connectional anatomy for the validation of diffusion MRI

Abstract: Despite the impressive advances in diffusion MRI (dMRI) acquisition and analysis that have taken place during the Human Connectome era, dMRI tractography is still an imperfect source of information on the circuitry of the brain. In this review, we discuss methods for post mortem validation of dMRI tractography, fiber orientations, and other microstructural properties of axon bundles that are typically extracted from dMRI data. These methods include anatomic tracer studies, Klingler's dissection, myelin stains,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 254 publications
(211 reference statements)
2
32
0
Order By: Relevance
“…This suggests that our in-plane angular errors are not biased by the presence of through-plane diffusion. Finally, the 2D angular errors in our PSOCT studies agree with both the 2D and 3D angular errors reported in studies that used histological staining, further supporting the validity of in-plane angular errors as a measure of accuracy (Anastasia Yendiki et al 2021).…”
Section: Limitationssupporting
confidence: 87%
See 3 more Smart Citations
“…This suggests that our in-plane angular errors are not biased by the presence of through-plane diffusion. Finally, the 2D angular errors in our PSOCT studies agree with both the 2D and 3D angular errors reported in studies that used histological staining, further supporting the validity of in-plane angular errors as a measure of accuracy (Anastasia Yendiki et al 2021).…”
Section: Limitationssupporting
confidence: 87%
“…There are several other techniques that have been used to assess the accuracy of dMRI orientation estimates. For a comprehensive discussion of their relative merits and weaknesses, we refer the reader to a recent review (Anastasia Yendiki et al 2021). One approach is to extract orientations from myelin-stained sections (Leergaard et al 2010;Choe et al 2012;K.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that long acquisition times are one of the main challenges in the post mortem validation of dMRI ( Yendiki et al, 2021 ), any opportunity to further reduce the scan time would be beneficial, as it would allow us to scan more samples or to scan the same samples at higher spatial resolution in the same amount of time. Compressed sensing (CS) has been proposed as an approach to accelerated DSI (CS-DSI).…”
Section: Introductionmentioning
confidence: 99%